Exploring the Terrains of Indonesian Cultural Policy: Learning from Singapore’s and Malaysia’s Experiences - Budi Irawanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article seeks to examine Indonesian cultural policy in comparison to Singapore and Malaysia. It focuses particularly on documentary films as a field covered by the cultural policy, which is closely associated with the creative industry. Therefore, this article analyzes various official documents regarding cultural policy and the position documentary films within that policy. While Singapore’s cultural policy is quite comprehensive and visionary in managing and regulating arts and culture, it tends to neglect documentary films as it celebrates commercial feature (fiction) films.  Similarly, Malaysian cultural policy pays scant attention to documentary films despite its nationalistic nature. Learning from those two neighboring countries, Indonesia should not only have a comprehensive cultural policy, but also a clear vision on the development of infrastructures while taking into account the fast changing ecology of documentary films in Indonesia.